Insider Power and Earnings Quality in the UK context - Aljalahma, Fatema (2016)
This study examines the relationship between the power of insiders (executives) and quality of earnings by the use of 210 non-financial UK firms from the index UK FTSE 350, covering the period 2012 until 2015. Power of insiders, is measured by the use of three factors: Board characteristics (size, composition and structure), audit and remuneration committee composition, and ownership (percentage of insider ownership and equal voting rights). The Modified Jones model was employed in the estimation of abnormal accruals as a proxy for earnings quality. The comparison considered and controlled for firms specific characteristics such as size, leverage, debt, growth and performance. The findings in this study show that the independence of the board of directors and audit committee increase the earnings quality in firms. Ownership gave mixed results as the percentage of insider ownership is positively related to earnings management, while voting rights have a negative effect. Whereas, the independence of the remuneration committee as well as the board of directors’ size and structure (measured as CEO duality) have no effect on earnings quality. Hence, I conclude that power of insiders in firms does increases the earnings management and having independent board and audit committee members reduces insider power and thereby increases the earnings quality.